Comparative lactic acid bacteria (LAB) profiles during dadih fermentation with spontaneous and back-slopping methods, as identified by terminal-restriction fragment length polymorphism (T-RFLP) - Chandra Utami Wirawati; Mirnawati Bachrum Sudarwanto; Denny Widaya Lukman; Ietje Wientarsih; Eko Agus Srihanto (Universitas Gadjah Mada, 2021)
The diversity of lactic acid bacteria (LAB) present during the manufacture of traditional fermented buffalo milk from West Sumatra, known as dadih, was studied via a culture-independent approach using terminal-restriction fragment length polymorphism (T-RFLP) to compare the dynamic diversity in back-slopping and spontaneous fermentation methods. Total LAB and pH were measured in freshly prepared buffalo milk and in dadih fermented for 24 and 48 hours. The results indicated significant differences between the fermentation methods, with higher total LAB, and greater phylotype richness and relative abundance being identified in the back-slopping method. Terminal fragment lengths (TRFs) of 68 and 310 bp were common to both techniques, similar to those of Lactobacillus fermentum, Fructobacillus pseudoficulneus, Leuconostoc citreum, Leuconostoc kimchii, and Leuconostoc sp. The changes in phylotype number (species number) and relative abundances of LAB communities identified are expected to produce data needed to formulate the best fermentation process for dadih manufacturing. A 24-hour back-slopping fermentation method is recommended, as fermentation time of longer than 24 hours reduced viable LAB significantly. Our results also indicated that the T-RFLP technique is not only clearly sensitive enough and adequate for segregating LAB diversity in both fermentation methods, but that it also provides good information regarding the structure of microbial communities and their composition change during the fermentation process.